Crystal structure and elastic properties of parabreyite: a new high-pressure ring silicate in the CaSiO3 system - B. Chrappan Soldavini; M. Merlini; M. Gemmi; P. Parlanti; P. Fumagalli; S. Milani; B. Joseph; G. Bais; M. Polentarutti; A. Kurnosov; S. Poli (European Journal of Mineralogy)
The CaSiO3 system exhibits notable structural complexity, featuring different polymorphs and polytypes across various pressure (P) and temperature (T) conditions compatible with Earth's environments. Among these, the pseudowollastonite and breyite structures are characterized by the presence of threefold tetrahedral rings. In this study, we conducted multianvil syntheses in the pressure and temperature range 4–5 GPa and 600–800 °C to stabilize crystals of a new high-pressure polymorph reported by Chatterjee et al. (1984) and obtain structural information. The structure was solved by combining 3D electron diffraction (ED) and synchrotron single-crystal X-ray diffraction (SC-XRD). The new high-pressure polymorph, here referred to as parabreyite, features threefold tetrahedral rings, with a different configuration compared to breyite. Parabreyite is triclinic, P<mover accent="true">1‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="765562c36c1bae1ee39e2fa60bf3bfd6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-13-2025-ie00001.svg" width="16pt" height="13pt" src="ejm-37-13-2025-ie00001.png"/></svg:svg>, with unit cell parameters a= 8.1911(10) Å, b= 9.3441(9) Å, c= 10.4604(10) Å, α= 73.901(8)°, β= 89.814(9)° and γ= 77.513(9)°. The bulk modulus, K0= 90.7(5) GPa, was determined by an in situ SC-XRD experiment using a diamond anvil cell (DAC) in the pressure interval 0–10 GPa. Thermal expansion was also determined by low- and high-temperature SC-XRD measurements and resulted in a larger value compared to breyite. Additionally, we performed in situ synchrotron SC-XRD on synthetic pseudowollastonite in the pressure interval 0–14 GPa and did not observe any structural phase transition in this ring-type polymorph. We also report the differences between the Raman spectra of parabreyite and breyite to help with the in situ identification of these polymorphs. The threefold ring topology of parabreyite suggests a new configuration for high-density tetrahedra structures, with significant implications for the prediction of high-pressure sp3 carbonates.